Whole-exome sequencing in a subject with fluctuating neuropsychiatric symptoms, immunoglobulin G1 deficiency, and subsequent development of Crohn’s disease: a case report - Jyonouchi, Harumi; Geng, Lee (Journal of medical case reports, 2022)
Mutations or polymorphisms of genes that are associated with inflammasome functions are known to predispose individuals to Crohn's disease and likely affect clinical presentations and responses to therapeutic agents in patients with Crohn's disease. The presence of additional gene mutations/polymorphisms that can modify immune responses may further affect clinical features, making diagnosis and management of Crohn's disease even more challenging. Whole-exome sequencing is expected to be instrumental in understanding atypical presentations of Crohn's disease and the selection of therapeutic measures, especially when multiple gene mutations/polymorphisms affect patients with Crohn's disease. We report the case of a non-Hispanic Caucasian female patient with Crohn's disease who was initially diagnosed with pediatric acute-onset neuropsychiatric syndrome with fluctuating anxiety symptoms at 9 years of age. This patient was initially managed with pulse oral corticosteroid treatment and then intravenous immunoglobulin due to her immunoglobulin G1 deficiency. At 15 years of age, she was diagnosed with Crohn's disease, following onset of acute abdomen. Treatment with oral corticosteroid and then tumor necrosis factor-α blockers (adalimumab and infliximab) led to remission of Crohn's disease. However, she continued to suffer from chronic abdominal pain, persistent headache, general fatigue, and joint ache involving multiple joints. Extensive gastrointestinal workup was unrevealing, but whole-exome sequencing identified two autosomal dominant gene variants: NLRP12 (loss of function) and IRF2BP2 (gain of function). Based on whole-exome sequencing findings, infliximab was discontinued and anakinra, an interleukin-1β blocker, was started, rendering marked improvement of her clinical symptoms. However, Crohn's disease lesions recurred following Yersinia enterocolitis. The patient was successfully treated with a blocker of interleukin-12p40 (ustekinumab), and anakinra was discontinued following remission of her Crohn's disease lesions. Loss-of-function mutation of NRLRP12 gene augments production of interleukin-1β and tumor necrosis factor-α, while gain-of-function mutation of IRF2BP2 impairs cytokine production and B cell differentiation. We propose that the presence of these two autosomal dominant variants caused an atypical clinical presentation of Crohn's disease.